A New Kind of Feminine: The Effects of the Icelandic Conversion on Female Religious Participation and the Image of the Feminine Divine - Ólöf Bjarnadóttir 1982- (2017)
This thesis is a study of how the conversion of Iceland to Christianity during the years surrounding the turn of the first millennium affected the religious participation of women and their perception of the feminine elements of the divine. Using a wide range of sources from a number of academic diciplines, it seeks to identify the roles and attributes specifically associated with the goddesses and the feminine supernatural forces known and worshipped as part of the Old Norse religions and to compare these to the image and role of the Christian Virgin Mary, Mother of God. The study then goes on to discuss how the changing religious environmet may have affected the involvement of women in religious practice and finally, it seeks to identify and consider what elements of the new Christian religion may have attracted Scandinavian and Icelandic women, encouraging them to turn away from the Old Norse religions.